Religious identity and delinquency: comparing Muslim, Christian and non-religious adolescents in the United Kingdom - Seto, Christopher H. (The British journal of criminology, 2022)
The relationship between religion and delinquency is shaped by sociocultural context, but little research has explored the relationship for non-Christian religions outside of the United States. This study advances existing scholarship by comparing the crime and illicit substance use of 9,772 Muslim, Christian and non-religious adolescents in the United Kingdom. The Karlson, Holm, Breen (KHB) method is used to explore underlying mechanisms. Results show that Muslims engage in the least delinquency, followed by Christians, while non-religious adolescents engage in the most delinquency. Religious involvement is especially protective for Muslim adolescents. These findings refute a pervasive public perception of Muslim identity as ‘risky’. KHB results reveal that educational motivation and parental supervision underlie religious group differences in delinquency.